Preparation method and application of graphite powder
By pressing and granulating the expanded graphite step by step, the high conductivity graphite powder is formed, which solves the problems of large internal resistance and limited capacity of existing alkaline batteries, and improves the battery capacity and reduces the internal resistance.
Patent Information
- Application Number
- CN202411628103.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The internal resistance of existing alkaline batteries is large, resulting in limited capacity, and the conductivity of traditional conductive graphite is low, resulting in high filling amount and reducing the content of positive electrode active substances.
By pressing the expanded graphite step by step, uniform and stable graphite particles are formed, and graphite powder with high conductivity is obtained by crushing.
It significantly improves the conductivity of graphite powder, reduces the internal resistance of the battery, and improves the capacity and performance of the battery.
Smart Images

Figure CN119430175A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of graphite materials, and in particular to a preparation method and application of graphite powder. Background Art
[0002] Alkaline batteries have become the first choice for electronic devices that require large discharge capacity and long-term use due to their long-lasting power. Existing alkaline batteries use manganese dioxide as the active substance of the positive electrode material, and add conductive graphite powder to improve the conductivity of the positive electrode. However, due to the low conductivity of traditional conductive graphite and the high filling amount required, the content of manganese dioxide in the positive electrode active material is reduced, which in turn leads to limited capacity of alkaline batteries and large internal resistance, generally around 500mΩ.
[0003] In order to improve the conductivity of conductive graphite and thus reduce the internal resistance of a battery prepared therefrom, the prior art uses flake graphite, sulfuric acid and hydrogen peroxide to carry out an oxidative intercalation reaction to prepare expandable graphite. After expansion to obtain the expanded graphite, the expanded graphite is crushed by a pulverizer to obtain graphite powder, or the expandable graphite is crushed and then expanded to obtain graphite powder. The product yield is low, the particle size after crushing fluctuates greatly, and the loose density is unstable. For batteries at the application end, the internal resistance is still relatively large. Summary of the invention
[0004] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the purpose of the present invention is to provide a method for preparing graphite powder, which directly forms graphite particles with stable bulk density by step-by-step pressing to prepare graphite powder with high electrical conductivity.
[0005] A second aspect of the present invention is to provide a positive electrode material.
[0006] The third aspect of the present invention is to provide an application of graphite powder or positive electrode material.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] A first aspect of the present invention provides a method for preparing graphite powder, comprising the following steps:
[0009] Granulating the expanded graphite to obtain graphite particles, and crushing to obtain graphite powder;
[0010] During the granulation process, the expanded graphite is subjected to a pressure of 0.2 to 1 times the target density of the graphite particles for 4 to 6 levels of step-by-step extrusion, with the pressure increasing step by step; the density of the graphite particles is 1 to 2 g / cm 3 ; The D50 of the graphite powder is 20 to 50 μm.
[0011] The present invention granulates expanded graphite by extruding it step by step at 4 to 6 levels within a specific pressure range, and controls the obtained graphite particles to have a uniform and stable density, so that the crushing effect is more uniform, the obtained graphite powder has good particle size consistency, and the specific surface area, tap density and loose density are stable, so that the conductivity of the graphite powder is improved, and the internal resistance of the battery can be significantly reduced when applied to the battery. However, the 1 to 3 level extrusion will cause some graphite particles to form bulges after molding, which is easy to cause large fluctuations in particle size during crushing, which is reflected in the battery as a reduced capacity and increased internal resistance.
[0012] At the same time, when the density value of the graphite particles exceeds the range of 1 to 2, the obtained graphite powder has poor uniformity and reduced conductivity. When used to prepare batteries, the capacity of the batteries is reduced, the internal resistance consistency is poor, and the battery yield is low.
[0013] In addition, by controlling the D50 of graphite powder, when it is used as a positive electrode filling conductive agent to prepare a battery, it can be better mixed with the positive electrode active material and improve battery performance.
[0014] The invention granulates the expanded graphite under specific conditions before pulverizing it, which can avoid the problem of uncontrollable particle size and difficulty in pulverizing to the required particle size during traditional granulation or direct pulverization, resulting in low production capacity and high cost. The method of the invention can achieve batch production by adjusting the granulation process, and has the advantages of controllable pulverized particles, large production capacity, low production cost, etc.
[0015] Preferably, the method for preparing the graphite powder does not include a pelletizing step.
[0016] Preferably, the D50 of the graphite powder is 30-50 μm.
[0017] Preferably, the pressure increment of the step-by-step extrusion is 0.1 to 0.3 times the target density of the graphite particles.
[0018] More preferably, the step-by-step extrusion is performed in 4 to 5 stages.
[0019] More preferably, the stepwise extrusion is performed in five stages, and the pressures are 0.2 to 0.3 times, 0.3 to 0.4 times, 0.45 to 0.6 times, 0.7 to 0.8 times, and 0.9 to 1 times the target density of the graphite particles, respectively.
[0020] More preferably, the die gaps corresponding to the five levels of progressive extrusion are 3-3.5 mm, 2.2-2.6 mm, 1.4-1.8 mm, 1-1.3 mm, and 0.6-0.8 mm, respectively.
[0021] Among them, the mold gap refers to the use of a mold to ensure the size of graphite particles during the granulation process. The mold is divided into two parts, an upper and a lower part. The upper and lower parts apply pressure at the same time for extrusion. As the extrusion proceeds, the gap between the upper and lower parts gradually decreases.
[0022] Preferably, the size of the graphite particles is a×b×c, wherein a is 0.8-1.2 mm; b is 4-6 mm; and c is 4-6 mm.
[0023] Preferably, the size of the graphite particles is ensured by a mold during the granulation process.
[0024] Preferably, the density of the graphite particles is 1 to 2 g / cm 3 .
[0025] Further preferably, the density of the graphite particles is 1 to 1.6 g / cm 3 .
[0026] More preferably, the density of the graphite particles is 1 to 1.5 g / cm 3 .
[0027] Preferably, the graphite powder can be obtained by directly crushing graphite particles, or by mixing graphite particles with natural graphite and then further crushing them, that is, making graphite particles into graphite powder includes the following steps: crushing the graphite particles to obtain graphite powder, or, mixing the graphite particles with natural graphite and then crushing them to obtain graphite powder.
[0028] Preferably, the graphite particles are mixed with natural graphite before the pulverization; and the D50 of the natural graphite is 0.01-0.2 mm.
[0029] More preferably, the D50 of the natural graphite is 0.04-0.08 mm.
[0030] Preferably, the graphite particles are mixed with natural graphite before the pulverization; the mass ratio of the graphite particles to natural graphite is 1:(0.1-1).
[0031] Further preferably, the mass ratio of the graphite particles to natural graphite is 1:(0.2-1), more preferably 1:(0.2-0.3).
[0032] By mixing graphite particles with natural graphite and then granulating them, the cost and performance of graphite powder can be balanced. The higher the amount of natural graphite used, the lower the cost, but the worse the performance of the graphite powder, the worse the battery performance obtained, so controlling the amount of natural graphite used can better balance the relationship between cost and performance.
[0033] Preferably, the expanded graphite is obtained by expanding expandable graphite; the expansion treatment is performed at the same temperature or in three stages; the temperature of the expansion treatment is ≤1000°C.
[0034] When the expansion treatment is divided into three stages, the temperature decreases gradually, and the decreasing range is 50 to 150°C.
[0035] Preferably, the method for preparing expanded graphite comprises the following steps:
[0036] The expandable graphite is subjected to a three-stage expansion treatment to obtain expanded graphite; the conditions of the three-stage expansion treatment are as follows:
[0037] The first stage: temperature 950~1000℃, time 0.2~1.2s;
[0038] The second stage: temperature 830-900°C, time 0.2-1.2s;
[0039] The third stage: temperature 750~820℃, time 0.2~1.2s.
[0040] In the present invention, the expandable graphite expands rapidly along the c-axis direction during the expansion process, the interlayer spacing increases by 100 to 1000 times, and after expansion, hollow particles (worms) with a length of 1 to 40 mm are formed. In this process, the control of the expansion temperature has a significant effect on the conductivity of the obtained graphite powder. If the temperature of any section is reduced, the sulfur content of the graphite particles and the graphite powder may increase, resulting in a decrease in the conductivity of the graphite powder, and an increase in the internal resistance of the battery finally obtained.
[0041] More preferably, the temperature of the first stage is 980-1000°C.
[0042] More preferably, the temperature of the second stage is 840-860°C.
[0043] More preferably, the temperature of the third stage is 790-810°C.
[0044] Preferably, the pulverizing method includes air flow pulverizing and / or mechanical pulverizing, more preferably air flow pulverizing.
[0045] Preferably, the crushing pressure is 0.5-1.5 MPa.
[0046] Using air flow crushing method to crush and control the crushing pressure can improve production capacity.
[0047] Preferably, the frequency of the classifier during the air flow milling process is 30 to 49 Hz, and more preferably 35 to 48 Hz.
[0048] Frequency adjustment of the classifier is one of the factors controlling the D50 of the crushed graphite powder.
[0049] Preferably, the expansion volume of the expandable graphite is 100 to 500 mL / g.
[0050] Preferably, the expandable graphite has a purity of ≥95% and a volatile matter content of ≤25%.
[0051] Preferably, the graphite powder satisfies at least one of the following a) to e):
[0052] a) Specific surface area is 15 to 35 m 2 / g;
[0053] b) Bulk density is 0.02~0.2g / cm 3 ;
[0054] c) Tap density is 0.1~0.4g / cm 3 ;
[0055] d) Magnetic material content ≤ 1ppm;
[0056] e) Sulfur content ≤ 1500ppm.
[0057] More preferably, the specific surface area of the graphite powder is 15 to 30 m 2 / g.
[0058] Further preferably, the bulk density of the graphite powder is 0.02 to 0.1 g / cm 3 , more preferably 0.05 to 0.1 g / cm 3 .
[0059] Further preferably, the tap density of the graphite powder is 0.11 to 0.35 g / cm 3 .
[0060] Further preferably, the content of magnetic substance in the graphite powder is 0.01 to 0.3 ppm.
[0061] More preferably, the sulfur content in the graphite powder is 100 to 880 ppm.
[0062] A second aspect of the present invention provides a positive electrode material, which includes graphite powder prepared by the preparation method described in the first aspect of the present invention.
[0063] The graphite powder obtained by the present invention has good specific surface area, loose density, tap density, and good particle size consistency. When used for preparing positive electrode materials, the contact area with the positive electrode material is increased, and the traditional point-to-point contact is changed to point-to-surface contact, and some areas can reach surface-to-surface contact. In addition, the graphite powder of the present invention has the characteristics of reduced graphite layers, increased pore structure, etc., which provide a good channel for the transmission of electrons between positive electrode material particles, enhance electrical conductivity, and the formed positive electrode material can improve battery performance.
[0064] The third aspect of the present invention provides an application of the graphite powder prepared by the preparation method described in the first aspect of the present invention or the positive electrode material described in the second aspect of the present invention in preparing a battery.
[0065] When the graphite powder of the present invention is used as a positive electrode material, it is distributed around the positive electrode active material, has a good specific surface area, low resistance and pore structure, increases the contact surface with the positive electrode active material, and facilitates the transmission of electrons to form a good conductive network, thereby improving battery performance. The graphite powder of the present invention can be mixed and filled with different conductive agents and is suitable for battery systems of different capacities.
[0066] Preferably, the batteries comprise alkaline batteries.
[0067] The alkaline battery positive electrode filled graphite powder provided by the present invention has a low resistivity. When the conductive graphite powder is applied to the alkaline battery, the filling amount of the conductive graphite powder in the positive electrode of the alkaline battery can be reduced, so that the alkaline battery not only has a high battery capacity and a low internal resistance, but also has a low leakage rate and can be stored for a long time.
[0068] Preferably, the capacity of the alkaline battery is 2000-3000 mAh, more preferably 2200-2500 mAh.
[0069] Preferably, the resistivity of the alkaline battery is 1 to 4 mΩ / cm, more preferably 2 to 3 mΩ / cm.
[0070] Preferably, the internal resistance of the alkaline battery is 50 to 130 mΩ, more preferably 50 to 100 mΩ.
[0071] Compared with the prior art, the present invention has at least the following beneficial technical effects:
[0072] The present invention provides a method for preparing graphite powder.
[0073] (1) The preparation method of the present invention adopts a step-by-step extrusion granulation process, and the obtained graphite particles have a uniform and stable density. The graphite powder obtained by crushing has good particle size consistency, stable specific surface area, and good pore structure. At the same time, the density of the graphite particles is controlled to ensure the uniformity of the graphite powder, and the D50 of the graphite powder is adjusted, which can improve the conductivity of the graphite powder. When applied to battery positive electrode materials, it can increase the battery capacity and reduce the internal resistance of the battery.
[0074] (2) The preparation method of the graphite powder of the present invention is first granulated under specific conditions and then crushed, which can achieve batch production and has the advantages of controllable crushed particles, large production capacity, low production cost, etc. Adjusting the crushing conditions can further increase the production capacity.
[0075] (3) The graphite powder obtained by the preparation method of the present invention has low resistivity, that is, high conductivity, good particle size uniformity, and good specific surface area, tap density and loose density. It can be used to prepare positive electrode materials, which is conducive to forming a good conductive network. The obtained battery has large capacity, low internal resistance, low leakage rate and long storage life. BRIEF DESCRIPTION OF THE DRAWINGS
[0076] Figure 1 This is the D50 particle size distribution diagram of 80 graphite powder samples prepared in Example 1.
[0077] Figure 2 This is a scanning electron microscope image of the graphite powder prepared in Example 1. DETAILED DESCRIPTION
[0078] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.
[0079] The expandable graphite used in the following examples and comparative examples of the present invention is obtained by the same preparation process, and the steps are as follows:
[0080] The flake graphite is washed with sodium hydroxide to remove impurities, and then washed with sulfuric acid, hydrochloric acid and hydrofluoric acid in sequence to remove impurities, and finally subjected to oxidation intercalation reaction with sulfuric acid and hydrogen peroxide to obtain expandable graphite (expansion volume of 100-500mL / g, purity>99%, volatile matter<25%); wherein the mass concentration of sodium hydroxide is 44%, the mass concentration of sulfuric acid is 98%, the mass concentration of hydrochloric acid is 31%, the mass concentration of hydrofluoric acid is 40%, and the mass concentration of hydrogen peroxide is 35%.
[0081] Example 1
[0082] This embodiment provides a method for preparing graphite powder, comprising the following steps:
[0083] The expandable graphite is expanded in three stages in an expansion furnace, wherein the temperature of the first stage is 1000°C and the time is 0.5-1s; the temperature of the second stage is 850°C and the time is 0.5-1s; the temperature of the third stage is 800°C and the time is 0.5-1s to obtain expanded graphite;
[0084] The expanded graphite uses negative pressure to suck the material into the silo, and then flows from the feeder to the granulation die. The granulation die is extruded step by step to 0.25 times, 0.35 times, 0.5 times, 0.75 times, and 1 times the target density value. The die gaps are 3.2mm, 2.4mm, 1.6mm, 1.2mm, and 0.6mm, respectively, forming a size of 1×5×5mm and a density of 1.3g / cm 3 of graphite particles;
[0085] The graphite particles are fed into the grinding chamber of the air flow mill by a jet feeding device. The air pressure is 0.6-1.0 MPa. The frequency of the classifier during the air flow milling process is 35 Hz. The air flow mill is milled to a D50 of 40-50 μm and a loose density of 0.05 g / cm 3 The graphite powder has a tap density of 0.133 g / cm 3 , the sulfur content is 703ppm and the magnetic material content is 0.112ppm.
[0086] Example 2
[0087] This embodiment provides a method for preparing graphite powder, which is the same as that of Embodiment 1, except that:
[0088] The graphite particles and flake graphite with a D50 of 0.06 mm were mixed in a mixer at a mass ratio of 1:1 and then crushed; the frequency of the classifier was 45 Hz; the graphite particles were crushed to D50 = 20-30 μm and a loose density of 0.08 g / cm 3 The graphite powder has a tap density of 0.308 g / cm 3 , the sulfur content is 870ppm and the magnetic material content is 0.214ppm.
[0089] Example 3
[0090] The embodiment provides a method for preparing graphite powder, which is the same as that of embodiment 1, except that:
[0091] The graphite particles and flake graphite with a particle size of 0.06 mm in D50 were mixed in a mixer at a mass ratio of 4:1 and then crushed; the frequency of the classifier was 48 Hz; the graphite particles were crushed to D50 = 20-30 μm and a loose density of 0.05 g / cm 3 The graphite powder has a tap density of 0.192 g / cm 3 , the sulfur content is 810ppm and the magnetic material content is 0.111ppm.
[0092] Comparative Example 1
[0093] This comparative example provides a method for preparing graphite powder, which is the same as Example 1, except that:
[0094] The classifier frequency is 50Hz, and the graphite particles are crushed to D50 = 10 ~ 30μm using a jet mill, and the bulk density is 0.04g / cm 3 The graphite powder has a tap density of 0.112 g / cm 3 , the sulfur content is 783ppm and the magnetic substance content is 0.118ppm.
[0095] Comparative Example 2
[0096] This comparative example provides a method for preparing graphite powder, which is the same as Example 1, except that:
[0097] The classifier frequency is 28Hz, and the graphite particles are crushed to D50 = 60 ~ 100μm using a jet mill, and the bulk density is 0.08g / cm 3 The graphite powder has a tap density of 0.182 g / cm 3 , the sulfur content is 805ppm and the magnetic material content is 0.124ppm.
[0098] Comparative Example 3
[0099] This comparative example provides a method for preparing graphite powder, which is the same as Example 1, except that:
[0100] Expanded graphite is made into a density of 0.8g / cm 3 The graphite particles are crushed into D50 = 30 ~ 50μm using a jet mill, and the bulk density is 0.05g / cm 3 The graphite powder has a tap density of 0.126 g / cm 3 , the sulfur content is 742ppm and the magnetic substance content is 0.109ppm.
[0101] Comparative Example 4
[0102] This comparative example provides a method for preparing graphite powder, which is the same as Example 1, except that:
[0103] The expanded graphite was extruded through a pelletizing die at 0.25 times, 0.5 times, and 1 times the target density (the die gaps were 3.2 mm, 1.6 mm, and 0.6 mm, respectively) to obtain a density of 1.3 g / cm 3 The graphite particles are crushed into D50 = 30 ~ 50μm using a jet mill, and the bulk density is 0.05g / cm 3 The graphite powder has a tap density of 0.141 g / cm 3 , the sulfur content is 832ppm and the magnetic substance content is 0.116ppm.
[0104] Comparative Example 5
[0105] This comparative example provides a method for preparing graphite powder, which is the same as Example 1, except that:
[0106] The three temperature and time stages of the expansion treatment of expandable graphite are: the temperature of the first stage is 850°C, the time is 0.5-1s; the temperature of the second stage is 700°C, the time is 0.5-1s; the temperature of the third stage is 650°C, the time is 0.5-1s, and the tap density of the graphite powder is 0.139g / cm 3 , the sulfur content is 931ppm and the magnetic substance content is 0.203ppm.
[0107] Results
[0108] The characteristic parameters of the graphite powder obtained in the above embodiments and comparative examples were tested:
[0109] (1) Specific surface area: measured according to the national standard GB / T 19587-2004;
[0110] (2) Bulk density: measured in accordance with the national standard GB / T 31057.1 2014.
[0111] (3) Tap density: measured in accordance with the national standard GB / T 21354-2008.
[0112] (4) Sulfur content: Measured in accordance with the national standard GB / T 3521-2023.
[0113] (5) Magnetic material content: measured in accordance with the national standard GB / T 24533-2019.
[0114] The graphite powder of the embodiment and the comparative example was used as a positive electrode conductive additive (the filling amount was 2wt% of the mass of manganese dioxide), and manganese dioxide was used as a positive electrode material to prepare an alkaline battery with a specification of No. 5 battery, and its battery capacity, internal resistance, resistivity and storage life were tested. The test method is as follows:
[0115] (6) Battery capacity: The battery capacity test adopts the constant current discharge experimental method. The test is carried out at an ambient temperature of 25°C. Specifically, a battery is discharged with a 3R resistor and a 10R resistor with a large current and a small current respectively. A multimeter is used to capture the battery discharge voltage curve and discharge current curve, so as to calculate the battery capacity.
[0116] Battery capacity = current × time, unit: mAh;
[0117] (7) Internal resistance: The resistance encountered by the current flowing through the battery when the battery is working. The internal resistance of a dry cell battery is tested using a voltmeter. The specific method is the volt-ampere method. By using the closed circuit Ohm's law E=U+Ir, the voltage U and current I at both ends of the battery can be measured to calculate the electromotive force E and internal resistance r of the battery. The specific steps are: Use a voltmeter and a resistor box to connect the circuit, adjust the resistance of the resistor box, and record the reading of the voltmeter; change the resistance of the resistor box, measure and record the readings of the voltmeter and ammeter multiple times; Based on the measured data, use the closed circuit Ohm's law to list a set of equations, and solve the electromotive force E and internal resistance r simultaneously.
[0118] (8) Resistivity: The four-probe method is used for testing. Four equally spaced probes are inserted into the semiconductor surface. A constant current source provides a suitably small current I to the two outer probes. The voltage V between the two middle probes is then measured. The resistivity of the semiconductor can be calculated. For a thin semiconductor sheet with a thickness of W (much smaller than the length and width), the resistivity is ρ = ηW (V / I), where η is the correction factor.
[0119] (9) Storage life: The maximum storage time allowed from the time the battery is manufactured to the time it is used.
[0120] The test results are shown in Table 1 below:
[0121] Table 1 Test results of graphite particles, graphite powder and prepared alkaline batteries in the embodiments and comparative examples
[0122]
[0123] As can be seen from Table 1, the graphite powder obtained in the embodiment of the present invention has good particle size consistency, stable specific surface area, moderate bulk density, can be used as a positive electrode conductive additive, and the resistivity does not exceed 3mΩ / cm. The battery capacity of the prepared alkaline battery is not less than 2200mAh, and the battery life is not less than 5 years. In addition, by testing the internal resistance of the battery, it is known that the internal resistance of the alkaline battery obtained by the graphite powder in Examples 1 to 3 of the present invention does not exceed 130mΩ, and can reach 60mΩ. In Example 2 and Example 3, different proportions of natural graphite were added respectively. In Example 2, the mass ratio of graphite particles to natural graphite reached 1:1, the proportion of natural graphite added was higher, the cost was reduced, and the internal resistance of the battery was significantly increased. Among them, although Example 1 has better performance, the cost is also higher than that of Examples 2 and 3.
[0124] In Comparative Examples 1 and 2, the particle size D50 of the graphite powder changes, D50 is smaller or larger, and the particle size uniformity is poor, it is not easy to disperse when preparing the battery, or the specific surface area is small, resulting in less contact area with the positive electrode active material and reduced battery performance.
[0125] According to the method of Example 1, 80 graphite powder samples were prepared, and the D50 particle size of these samples was analyzed by a laser particle size analyzer. The results are as follows Figure 1 shown. Figure 1 The D50 particle size distribution diagram of 80 graphite powder samples prepared in Example 1 shows that D50 is stably distributed in the range of 40 to 50 μm, and the particle size distribution is stable and consistent.
[0126] In summary, the graphite powder provided by the present invention has good particle size consistency, stable specific surface area, and good pore structure, which realizes the improvement of the conductivity of the graphite powder, can be used to prepare positive electrode materials, is conducive to forming a good conductive network, and the obtained battery has large capacity, low internal resistance, low leakage rate, and long storage life. At the same time, the preparation method of the graphite powder of the present invention can realize batch production, and has the advantages of controllable crushed particles, large production capacity, and low production cost.
[0127] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing graphite powder, characterized in that: The steps include: Granulating the expanded graphite to obtain graphite particles, and crushing to obtain graphite powder; During the granulation process, the expanded graphite is subjected to a pressure of 0.2 to 1 times the target density of the graphite particles for 4 to 6 levels of step-by-step extrusion, with the pressure increasing step by step; the density of the graphite particles is 1 to 2 g / cm 3 ; The D50 of the graphite powder is 20 to 50 μm.
2. The preparation method according to claim 1, characterized in that: The pressure increment of the step-by-step extrusion is 0.1 to 0.3 times the target density of the graphite particles.
3. The preparation method according to claim 1 or 2, characterized in that: The size of the graphite particles is a×b×c, wherein a is 0.8-1.2 mm, b is 4-6 mm, and c is 4-6 mm.
4. The preparation method according to claim 1 or 2, characterized in that: The graphite particles are mixed with natural graphite before the pulverization; the D50 of the natural graphite is 0.01-0.2 mm; And / or, the graphite particles are mixed with natural graphite before the pulverization; the mass ratio of the graphite particles to natural graphite is 1:(0.1-1).
5. The preparation method according to claim 1, characterized in that: The preparation method of the expanded graphite comprises the following steps: The expandable graphite is subjected to a three-stage expansion treatment to obtain expanded graphite; the conditions of the three-stage expansion treatment are as follows: The first stage: temperature 950~1000℃, time 0.2~1.2s; The second stage: temperature 830-900°C, time 0.2-1.2s; The third stage: temperature 750-820°C, time 0.2-1.2s.
6. The preparation method according to claim 1, characterized in that: The pulverizing method includes air flow pulverizing and / or mechanical pulverizing; And / or, the crushing pressure is 0.5 to 1.5 MPa.
7. The preparation method according to claim 1 or 5, characterized in that: The expansion volume of the expandable graphite is 100 to 500 mL / g; And / or, the expandable graphite has a purity of ≥95% and a volatile matter content of ≤25%.
8. The preparation method according to claim 1 or 6, characterized in that: The graphite powder satisfies at least one of the following a) to e): a) Specific surface area is 15 to 35 m 2 / g; b) Bulk density is 0.02~0.2g / cm 3 ; c) Tap density is 0.1~0.4g / cm 3 ; d) Magnetic material content ≤ 1ppm; e) Sulfur content ≤ 1500ppm.
9. A positive electrode material, characterized in that: The positive electrode material comprises graphite powder prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the graphite powder prepared by the preparation method according to any one of claims 1 to 8 or the positive electrode material according to claim 9 in preparing a battery.
Citation Information
Patent Citations
Dimensionally stable, leak-free graphite substrate
CN101563219A
Conductive graphite powder as well as preparation method and application thereof
CN115432701A
High-thermal-conductivity flexible graphite plate and preparation method thereof
CN117466644A
Six-group roller type granulator
CN221334031U
Plant for manufacturing heat-distributing material
RU2666411C1